Sistem Informasi Pendataan Atlet Berbasis Web Di Koni Kabupaten Pesisir Selatan - Siti Hasanah; April Zahmi (Ekasakti Jurnal Penelitian dan Pengabdian, 2025)
Athlete data management is an essential aspect of sports development, particularly for organizations such as the Indonesian National Sports Committee (KONI). In KONI Pesisir Selatan Regency, athlete data collection has traditionally been conducted manually, leading to various issues such as delays in information processing, data entry errors, and difficulties in archiving. This study aims to design and develop a web-based athlete data management information system to improve efficiency and accuracy in data handling. The development method applied is the Waterfall model, which includes stages of problem identification, data collection, requirements analysis, system design, implementation, and testing. The system was implemented using PHP as the programming language and MySQL as the database. Testing was carried out using the Black Box Testing method, and the results showed that all system functions operated as intended, including athlete and coach data management, training schedules, and report generation. This system has proven to enhance speed, accuracy, and organization in athlete data management compared to the previously used manual method.